Balanced scorecard in the hospitality and tourism industry: Past, present and future - Tahniyath Fatima (16500229) (2020)
After its introduction in 1992, the balanced scorecard (BSC) has attracted considerable interest from both scholars and practitioners. This is evidenced by the increasing number of publications addressing BSC and the large number of professional events devoted to it. However, there is little research on BSC in the hospitality and tourism industry. This study aims to contribute towards filling this significant gap through studying 106 top-ranked journal articles on BSC, of which 37 belong to the hospitality and tourism industry. In so doing, the study highlights the research focus that has been placed so far on BSC and examines its trends and the relationships amongst its perspectives. It also provides valuable input to identify gaps currently impeding BSC development in the hospitality and tourism industry, recommends future research opportunities intended to improve understanding and practice of BSC along with building up on emerging research topics like sustainable tourism and new tourism management. Other Information Published in: International Journal of Hospitality Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhm.2020.102656